FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT PEMANFAATAN SISTEM INFORMASI PADA DOSEN JURUSAN TEKNIK ELEKTRO POLSRI - Irma Salamah; RD Kusumanto (Jurnal Digit, 2015)
The information system has been widely utilized in various fields including the field of education. This study aims to examine the factors that affect the interests of academic information system utilization in electrical engineering lecturer POLSRI totaling 71 people. The data in this study was obtained from the primary data and secondary data. Primary data were obtained through a questionnaire (questionnaire) that has been provided. Secondary data were obtained from the administrative department of electrical engineering polytechnic sriwijaya. All lecturers sampled. A total of 71 questionnaires given and everything back. The data were analyzed using multiple linear regression techniques. These results indicate that the performance expectancy, effort expectancy and social factors affect the behavioral intention of academic information systems. This is because the respondents felt the information system helps in improving the quality of work and more improve the quality of teaching and learning. The background of the respondents who have educational S2 is also a supporter so it does not feel difficult in using the existing academic information system. Besides superiors and co-workers also strongly supports the use of existing academic information system. Keywords : behavioral intention, performance expectancy, effort expectancy, social factor